2018
DOI: 10.1371/journal.pntd.0006680
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dog population contact network structures in rabies transmission

Abstract: Canine rabies transmission was interrupted in N’Djaména, Chad, following two mass vaccination campaigns. However, after nine months cases resurged with re-establishment of endemic rabies transmission to pre-intervention levels. Previous analyses investigated district level spatial heterogeneity of vaccination coverage, and dog density; and importation, identifying the latter as the primary factor for rabies resurgence. Here we assess the impact of individual level heterogeneity on outbreak probability, effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 44 publications
4
82
0
Order By: Relevance
“…In Japan, the companion dog population is estimated to be 8.9 million and about 13% of the households own at least one dog; the most popular dog breeds are small‐breed dogs such as miniature dachshund, Chihuahua, toy poodle and shiba‐inu (JPFA, ). Various studies both in Japan and overseas have examined the epidemiology of dog walking and its associated health benefits, while recent studies have focussed on the interaction and contact rate between domestic dogs with particular reference to rabies (Christian et al, ; Hidano, Hayama, & Tsutsui, ; Laager et al, ; Oka & Shibata, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the companion dog population is estimated to be 8.9 million and about 13% of the households own at least one dog; the most popular dog breeds are small‐breed dogs such as miniature dachshund, Chihuahua, toy poodle and shiba‐inu (JPFA, ). Various studies both in Japan and overseas have examined the epidemiology of dog walking and its associated health benefits, while recent studies have focussed on the interaction and contact rate between domestic dogs with particular reference to rabies (Christian et al, ; Hidano, Hayama, & Tsutsui, ; Laager et al, ; Oka & Shibata, ).…”
Section: Introductionmentioning
confidence: 99%
“…Global sensitivity analysis indicated that population size (a parameter of reasonable certainty) and degree of connectivity had the greatest influence on duration, size and initial spread; this makes intuitive sense, and as expected, the largest and longest outbreaks were predicted in the Warraber network which had the highest median degree. Degree distribution might vary between populations of free-roaming dogs; however, a study in N’Djaména, Chad, found that the average degree was 9 and 15 (maximum 20 and 64, respectively) in two populations of size 272 and 237 dogs, respectively (19), which is not dissimilar to the Torres Strait dog populations. Reassuringly, input parameters about which there was more uncertainty – for example, bite probabilities – were less influential on variation in outputs.…”
Section: Discussionmentioning
confidence: 97%
“…Without behavioural change, we could not demonstrate rabies propagation in the social networks in the current study; disruption of social contacts appears to be key for rabies maintenance in small populations of dogs. Social network studies have shown that dogs form contact-dense clusters (12, 19). Increased bite probability and spatio-temporal association between contacts (edge-weight in the model) were most influential in our model, but it is possible that ‘re-wiring’ of dogs is also influential in larger populations in which there is a greater probability that a dog would ‘re-wire’ to completely new set of dogs in another cluster, thus increasing total contacts and enhancing spread (degree was also found to be highly influential on rabies spread).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations